MCM-GINS and MCM-MCM interactions in vivo visualised by bimolecular fluorescence complementation in fission yeast - MacNeill Stuart A; Akman Gökhan (BMC Cell Biology, 2009)
Abstract Background Each of the three individual components of the CMG complex (Cdc45, MCM and GINS) is essential for chromosomal DNA replication in eukaryotic cells, both for the initiation of replication at origins and also for normal replication fork progression. The MCM complex is a DNA helicase that most likely functions as the catalytic core of the replicative helicase, unwinding the parental duplex DNA ahead of the moving replication fork, whereas Cdc45 and the GINS complex are believed to act as accessory factors for MCM. Results To investigate interactions between components of the CMG complex, we have used bimolecular fluorescence complementation (BiFC) in the fission yeast Schizosaccharomyces pombe for the first time, to analyse protein-protein interactions between GINS and MCM subunits expressed from their native chromosomal loci. We demonstrate interactions between GINS and MCM in the nuclei of exponentially-growing fission yeast cells and on chromatin in binucleate S-phase cells. In addition we present evidence of MCM-MCM interactions in diploid fission yeast cells. As with GINS-MCM interactions, MCM-MCM interactions also occur on chromatin in S-phase cells. Conclusion Bimolecular fluorescence complementation can be used in fission yeast to visualise interactions between two of the three components of the CMG complex, offering the prospect that this technique could in the future be used to allow studies on replication protein dynamics in living S. pombe cells.